Neonatal platelets: mediators of primary hemostasis in the developing hemostatic system - Haley, Kristina M. (Pediatr Res, 2014)
The human hemostatic system is developmentally regulated, resulting in qualitative and quantitative differences in the mediators of primary and secondary hemostasis as well as fibrinolysis in neonates and infants. Although gestational and age related differences in coagulation factor levels occur, the existence of a unique neonatal platelet phenotype remains controversial. Complicated by difficulties in obtaining adequate neonatal blood volumes with which to perform functional assays, ambiguity surrounds the characterization of neonatal platelets. Thus, much of the current knowledge of neonatal platelet function has been based on studies from cord blood samples. Studies suggest that cord blood-derived platelets, as a surrogate for neonatal platelets, are hypo-functional when compared to adult platelets. This relative platelet dysfunction combined with a propensity toward thrombocytopenia in the Neonatal Intensive Care Unit population, creates a clinical conundrum regarding the appropriate administration of platelet transfusions. This review provides an appraisal of the distinct functional phenotype of neonatal platelets. Neonatal platelet transfusion practices and the impact of the relatively hypo-functional neonatal platelet on those practices will be considered.